PROFIL PEMECAHAN MASALAH PADA MATERI PERSAMAAN LINIER SATU VARIABEL DENGAN MENGGUNAKAN PENDEKATAN MODEL ELICITING ACTIVITIES (MEAs) DILIHAT DARI KEMAMPUAN MATEMATIKA - Anita Rahayuningrum1; Fariz Setyawan; Uswatun Khasanah (AlphaMath : Journal of Mathematics Education, 2018)
The purpose of this study is to know the problem-solving profile in Linear Equation of OneVariable (LEOV) by using Model Eliciting Activities (MEAs) based on the student’smathematics ability. This study is a descriptive qualitative research. The subjects of the studyare chosen by using purposive sampling and 7th grade junior high school students are selectedas the sample of the research. Furthermore, the data is classified into two categories, there arethe students with high and low mathematics ability categories. The data was analyzed anddescribed as the mathematics problem-solving profile based on Polya’s four steps method.The result of the study shown that the subject with high mathematics ability solved theproblem using all the Polya’s four steps method. The initial step derived by the subjects wereunderstanding the problem. Next, the subjects wrote the given information, the question, andthe missing data while they were solving the problem. In the carrying out the plan, thestudents perform any necessary actions such as formulating, modelling and computations.The problem was well-formulated by using appropriate steps and well-described in eachprocedure. The computation derived by the subject was examined after conclusion. Theappropriate computation derived by the subject attains well-outcomes. The obtained numbersare well described in each step of solving the given problem. It implies that the indicator ofproblem-solving were achieved based on the given description. However, the subjects withlow categories were lack to describe the devising strategy while solving the given problems.